2014
DOI: 10.2341/12-377-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Radiopacity of Dental Composites on the Diagnosis of Secondary Caries: The Correlation Between Objective and Subjective Analyses

Abstract: SUMMARY This study aimed to objectively evaluate the radiopacity of different dental composites and their subjective influence on diagnosing secondary caries–like lesions and how these results correlate. For objective analysis, three resin specimens (1 mm thick, with a 4-mm internal diameter) were made with four composites: 1) Charisma; 2) Filtek Z250; 3) Prisma AP.H; and 4) Glacier. Three human teeth were selected and then mesio-distally sectioned (1 mm thick) to make the dental specimens. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 18 publications
2
28
0
5
Order By: Relevance
“…According to Cruz et al, an ideal radiopacity for dental composites is one that is closer to the dentin image and which ultimately produces a similar attenuation to that of sound dentin tissue 29) . Excessively radiopaque restorations may hinder a clinician's ability to spot marginal defects due to the Mach effect 30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cruz et al, an ideal radiopacity for dental composites is one that is closer to the dentin image and which ultimately produces a similar attenuation to that of sound dentin tissue 29) . Excessively radiopaque restorations may hinder a clinician's ability to spot marginal defects due to the Mach effect 30) .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical situations, diagnostic challenges arise when radiographic images present barely discernible radiopacity differences between dental tissues and restorative materials 8,29) . According to Cruz et al, an ideal radiopacity for dental composites is one that is closer to the dentin image and which ultimately produces a similar attenuation to that of sound dentin tissue 29) .…”
Section: Discussionmentioning
confidence: 99%
“…5,24 However, an adjustment in characteristic curves of the images can occur, because photostimulable phosphor digital systems use a histogram equalization algorithm (automatic range control) during image acquisition, which corrects the contrast from the images. 24 Histogram equalization algorithm is very important, because these systems own high latitude, which makes it possible to deviate from the optimal exposure and continue generating images that are subjectively very similar.…”
Section: Discussionmentioning
confidence: 99%
“…5 The human eye has a wide dynamic range to luminous intensity, and it can distinguish between the different shades only if subsequent intensities of shades differ by .1%, 6 with the underlying visual response varying in dependence of stimulus context at the luminance-to-lightness mapping. 23 A previous study 5 reported that, when radiographic images of composites were evaluated for recurrent caries diagnosis, even if only insignificant differences in radio-opacity existed, they were able to somewhat influence a radiographic diagnosis. In the present study, a variation very close to the radio-opacity described by pixel-intensity values was observed among the different resin composites, showing no statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation